Assessment of knowledge and menstrual hygiene management among adolescent school girls of Nelamangala - M., Kavitha; Jadhav, Jyothi; T. S., Ranganath; ., Vishwanatha (International Journal Of Community Medicine And Public Health, 2018)
Background: Menstruation is a physiological process but generally it is considered as unclean in the Indian society. Hygiene related practices of menstruation are of considerable importance as it has health impact in terms of increased vulnerability to reproductive tract infections (RTI) and drop outs from school. A good knowledge regarding menstrual hygiene is important during adolescence age which helps to practice good hygiene, minimize the sufferings of women and to manage their menstruation without any hesitation. Methods: A cross sectional study was undertaken in a rural field practice area of BMCRI, Bengaluru. Data was collected from 311 adolescent girls by using predesigned semi structured questionnaire. Results: It was evident that 38.3% participants were aware about menstruation before their menarche and among them; mothers were the main source of the information for 72.3% girls. It was found that 80.4% respondents used sanitary pads and 73.6% girls did not have practice of changing the adsorbent in the school. Only 27.7% had the practice of changing ≥4 pads/cloths per day during the menstruation. Majority of the girls were restricted to enter the place of worship (73.3%) and to attend the religious functions (41.5%) and also restriction to eat certain food items among 20.3% girls. There was a significant association between the religion and the frequency of changing the adsorbent and cleaning the external genitalia during the menstrual period. Conclusions: This study could found that majority of the girls had no information about menstruation before menarche. Menstrual hygiene management (MHM) was very poor.